2006
DOI: 10.1577/t05-237.1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Diversity of Lake Trout in Great Slave Lake: Differences in Morphology, Buoyancy, and Habitat Depth

Abstract: Little is known about the phenotypic diversity of lake trout Salvelinus namaycush in large North American lakes outside the Laurentian Great Lakes. This study tested the hypothesis that phenotypic diversity in Great Slave Lake, Northwest Territories, Canada, is associated with water depth, as was observed during similar studies of lake trout in Lake Superior. We describe the association of body size with color, buoyancy, and morphology; compare these phenotypic traits among depth strata; and establish whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 58 publications
6
114
1
Order By: Relevance
“…Thus, the divergence of GBL Lake Trout into discrete morphs is likely, at least partially, related to selection acting on traits important for food exploitation (or habitat use associated with prey distribution). Variation in depth-related habitat use and diet has also been associated with ecotypic/morphological variation in this species in other northern systems (Zimmerman et al, 2007) including GSL (Zimmerman et al, 2006(Zimmerman et al, , 2009. GSL has likely shared a similar glacial history to that of GBL, and Lake Trout from these two systems have likely been isolated for approximately 8500 years (Smith, 1994).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, the divergence of GBL Lake Trout into discrete morphs is likely, at least partially, related to selection acting on traits important for food exploitation (or habitat use associated with prey distribution). Variation in depth-related habitat use and diet has also been associated with ecotypic/morphological variation in this species in other northern systems (Zimmerman et al, 2007) including GSL (Zimmerman et al, 2006(Zimmerman et al, , 2009. GSL has likely shared a similar glacial history to that of GBL, and Lake Trout from these two systems have likely been isolated for approximately 8500 years (Smith, 1994).…”
Section: Discussionmentioning
confidence: 90%
“…More recently, however, additional examples of within-lake morphological divergence in Lake Trout have been described throughout the geographical range of this species (Zimmerman et al, 2006(Zimmerman et al, , 2007Northrup et al, 2010) including relatively unperturbed systems from the Canadian Arctic. For example, in Great Bear Lake (GBL; Figure 1), Canada's largest, virtually pristine system, Blackie et al (2003) showed that Lake Trout characterized as 'piscivorous' and 'insectivorous' based on diet that were captured in shallow-water habitats (o20 m) could be differentiated morphologically based largely on differences in upper and lower jaw length, pectoral fin length and caudal peduncle depth.…”
Section: Introductionmentioning
confidence: 99%
“…1). More recently, researchers have identified lakes with more than one lake charr morphotype (hereafter morph): Great Bear Lake, NWT (Blackie et al 2003;Alfonso 2004); Great Slave Lake, NWT (Zimmerman et al 2006); Lake Mistassini, QC (Zimmerman et al 2007). These three lakes ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lake charr, like other Salmonidae such as Arctic charr (S. alpinus) (GĂ­slason et al 1999) and various whitefishes (Coregonus) (Turgeon et al 1999), is capable of morphological divergence under certain conditions. The isolating mechanisms responsible for divergent evolution of lake charr morphs are not well understood, in part, because in comparison to the well-studied Arctic charr (e.g., SkĂşlason et al 1996) most of the literature on ecological, morphological, or genetic variations among forms (e.g., Lindsay 1964; Khan and Qadri 1970;Behnke 1972;Krueger and Ihssen 1995;Harvey and Kitchell 2000;Bronte et al 2003;Page et al 2004;Zimmerman et al 2006) focuses on one lake-Superior. This uneven treatment of populations is a barrier to identifying patterns, if any, of morphological divergence in lake charr among lakes.…”
Section: Introductionmentioning
confidence: 99%
“…Buoyancy was used as one physiological indicator of habitat and prey use. Per cent buoyancy accounts for differences in density and relative quantity of soft versus hard tissues that affect the specific gravity of the fish (Alexander 1972) and is positively correlated with body lipid content and depth of capture in many fishes (Zimmerman et al 2006). High body lipid content is a more energy-efficient adaptation than the swim bladder for facilitating vertical migration in deepwater fishes (Alexander 1972(Alexander , 1993.…”
Section: Character Acronym Definitionmentioning
confidence: 99%